PROTECTING THE HARMONY – THOUGHTS ON THE MARGIN OF ANGI ISTVÁN’S BOOK ABOUT AESTHETIC PIETY (ANGI ISTVÁN: A HARMÓNIA MARAD, PARTIUM KIADÓ, NAGYVÁRAD, 2013) - Attila FODOR (Studia Universitatis Babeş-Bolyai. Musica)
Seems like it was only yesterday, when we have celebrated the 70th birthday of the restless and prolific music esthetician from Cluj-Napoca, Angi István, with the presentation of his book edited by the Polis Publising, entitled The models of the musical beauty. Since then a decade has gone, but not in vain, since the author contributed consistently with Romanian and Hungarian works to the domestic literature of music aesthetics, otherwise not too abundant. While these books develop certain aspects of the author’s well-known grotesque-transcendent aesthetic system, including its adaptation to the modern and contemporary musical art, the esthetician returns in this jubilee publication to the main subject of the already mentioned book entitled The holiest music. The sacred field of the sound art situated beyond the proper aesthetic, which became for Angi István a lifelong revelation in the catching beauty of the transcendence music experience from the childhood lauds to the practice of Gregorian chant in the recent past, gives birth to this book solely devoted to the aesthetic piety.